The Influence Of Recruitment, Transformational Leadership, And Employee Engagement To Employee Performance - Vabilla, Tanti; Ramli, Abdul Haeba (CV. ULIL ALBAB CORP, 2026)
In the current era of globalization and digitalization, companies are required to have superior human resources, where recruitment and transformational leadership are the key to improving employee engagement and employee performance. This study aims to analyze the influence of recruitment and transformational leadership on employee engagement and employee performance in manufacturing employees in Tangerang. The method used in this study is a quantitative approach with a survey of 145 respondents through the distribution of online questionnaires using Google Forms and analyzed using SEM-PLS. The results of the study indicate that recruitment and transformational leadership have a positive impact on employee engagement and employee performance. This study suggests that companies improve the quality of the recruitment process and the implementation of transformational leadership to create a work environment that supports employee engagement. The theoretical contribution of this study proves the role of recruitment and transformational leadership in positively influencing employee engagement and employee performance, while its practical contribution is strategic advice in human resource management to improve overall organizational performance.